Environments (out) of Control - Lorinc Vass; Roy Cloutier; Nicole Sylvia; Contingent Collective (Footprint)
This article examines the contradictory circuits of (neo)cybernetics in contemporary architectural and urbanistic discourse by reframing them within the ‘environmentalitarian’ epoch. Cybernetics is today simultaneously exalted as a liberatory mechanism for designing emergence, complexity and open-endedness, and constitutive of an indiscernible mode of decentralised, environmentally modulated control. The history of cyberneticisation has received renewed attention as the key catalyst for environmentalisation, and as the predominant control paradigm underlying late-capitalist Environmentality. Given the profound spatial implications of this trajectory, understanding architecture’s own cybernetic entanglements is a much-needed step towards a critical revaluation of environmentality. The article thus maps the cybernetic imaginary ‘at large’ across architecture – alongside landscape architecture and urbanism – under various guises such as adaptation, responsiveness, cultivation, resilience or conversation. By probing the salient characteristics of these approaches, their problematic proximity to the logic of cybernetic capitalism is contextualised in relation to the broader ontological and ontopolitical questions of the Anthropocene era. The article concludes by tracing possible conceptual trajectories amid and beyond the restrictive circuits of Environmentality: from adaptation to contingency, via Yuk Hui’s proposal for a cosmopolitics grounded in affirmative fortuity; and from responsiveness to response-ability, via Donna Haraway’s experimental material-semiotics of sympoiesis.